1997
DOI: 10.1161/01.res.81.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Vascular Remodeling in the Rat Carotid Artery Diminishes With Age

Abstract: Vascular remodeling is regulated by a combination of hemodynamic, environmental, and genetic factors and may be influenced by age. To evaluate age-dependent remodeling in rats, we developed and used a quantitative highly reproducible model of carotid flow alteration. Fourteen juvenile (99+/-3 g) and 9 adult (199+/-5 g) male inbred Fischer rats underwent ligation of the left internal and external carotid arteries under anesthesia. Left common carotid blood flow immediately decreased by approximately 93%, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
73
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 28 publications
14
73
0
2
Order By: Relevance
“…This age‐dependent remodeling was also observed in rats in which ligation of the left internal and external carotid arteries increased right carotid blood flow by 46%. After 4 weeks, the right carotid outer diameter increased and shear stress returned to initial values in juvenile but not adult rats 76. The constrained arterial remodeling and augmented shear stress set point of aged animals is strikingly similar to the phenotype we observed in nonreversed flow collateral segments.…”
Section: Discussionsupporting
confidence: 78%
“…This age‐dependent remodeling was also observed in rats in which ligation of the left internal and external carotid arteries increased right carotid blood flow by 46%. After 4 weeks, the right carotid outer diameter increased and shear stress returned to initial values in juvenile but not adult rats 76. The constrained arterial remodeling and augmented shear stress set point of aged animals is strikingly similar to the phenotype we observed in nonreversed flow collateral segments.…”
Section: Discussionsupporting
confidence: 78%
“…These findings demonstrate significant strain-dependent differences in shear stress regulation and vascular remodelling in response to altered flow. Like our previous study (42) in Fischer rats, there was no change in media area and no neointima formation. However, we have chosen mice for our genetic analysis because the magnitude of the phenotypic differences (measured by changes in vessel wall components) was much greater.…”
Section: Flow-dependent Remodelling In Rats Is Genetically Determinedsupporting
confidence: 80%
“…Key requirements for our model included the ability to study both high and low flow, reproducibility, technical ease in establishing the change in flow, availability of multiple inbred strains, ability to perform physiological measurements, a sequenced genome with multiple polymorphic markers and low cost. Initially, we focused on rats because their larger size permitted development of the procedure and validation of the remodelling mechanism (41,42).…”
Section: Flow-dependent Remodelling In Rats Is Genetically Determinedmentioning
confidence: 99%
See 1 more Smart Citation
“…27,30,41,42 In the present study, we observed flowinduced outward hypertrophic remodeling but no hypotrophy in resistance arteries exposed to low blood flow in normotensive Wistar rats studied between 10 and 14 weeks of age. This indicates dependence of flow-related arterial remodeling on rat age 43 and strain. 44 Unexpectedly, no significant differences in diameter and media mass were observed between control arteries and arteries Flow-induced remodeling in DOCA-salt hypertension P Lemkens et al exposed to elevated blood flow for 7 weeks in normotensive rats.…”
Section: Discussionmentioning
confidence: 78%